2023
DOI: 10.1002/vms3.1099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aloe vera (Aloe barbadensis M.) as an alternative to antibiotics on the growth performance, carcass characteristics and haemato‐biochemical indices of broiler chickens

Abstract: Background: Medicinal herbs as classes of additives to poultry feeds have proven to be beneficial due to their antioxidant, antimicrobial and antifungal properties.Objective: A 6-week study was conducted to assess the effects of Aloe vera (Aloe barbadensis M.) as an alternative to antibiotics on the growth performance, carcass traits and haemato-biochemical parameters of broiler chickens.Methods: A total of 240 unsexed commercial broiler chickens, 2 weeks old, were randomly allocated to four treatments: T1 (ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Its anti-inflammatory properties will shield teeth wounds from discomfort and hasten their healing. This ability will support aloe barbadensis in its use as a supplement to support tooth and bone growth (Quaye et al, 2023).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Its anti-inflammatory properties will shield teeth wounds from discomfort and hasten their healing. This ability will support aloe barbadensis in its use as a supplement to support tooth and bone growth (Quaye et al, 2023).…”
Section: Resultsmentioning
confidence: 98%
“…The smell that was detected is the characteristic scent of Aloe barbadensis; it is similar to the scent of grass and is unique to Aloe barbadensis alone. The reason for the liquid extract form is that distilled water is added to Aloe barbadensis to increase its dominance, resulting in a liquid extract (Quaye et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that the relationship between AVG levels and erythrocyte count followed a negative quadratic trend, with an optimal level of AVG that maximized the erythrocyte count calculated as 2.83%. Quaye et al ( 2023 ) noted higher levels of erythrocyte count in 42-day-old Cobb 500 broilers supplemented with AVG extract at 1% compared to the control groups. The authors attributed the increase to the erythropoietin effects of AVG on hemopoietic cells in the bone marrow, which can improve erythrocyte production (Iji et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown antibacterial, antiseptic, antiinflammatory and immune-modulator effects of Aloe vera (El-Kholy et al, 2022). Many studies have also shown antioxidant and anti-cancerous properties of Aloe vera (Abo El-Azayem et al, 2023;Quaye et al, 2023).…”
Section: Introductionmentioning
confidence: 99%